2018
DOI: 10.1016/j.diii.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cannabis and tobacco on emphysema in patients with spontaneous pneumothorax

Abstract: The prevalence of emphysema visible on CT is not different between tobacco and tobacco/cannabis smokers, however, it occurs at a younger age in tobacco and cannabis smokers. This result suggests that cannabis, when added to tobacco, may lead to emphysema at a younger age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…This is in contrast to a case series of 10 patients which found asymmetrical bullous changes on CT among chronic marijuana smokers but with normal spirometry and chest radiographs [37]. A study looking at smoking status and the presence of emphysematous computed tomography changes of spontaneous pneumothorax patients found no difference in emphysema prevalence among tobacco smokers and tobacco plus cannabis smokers (there were no cannabis only smokers); however, concurrent smokers were significantly younger [49]. While the authors have suggested that cannabis added to tobacco leads to emphysema at a younger age, there are too many confounders such as the subject population, to come to a definitive conclusion.…”
Section: Bullous Lung Diseasementioning
confidence: 60%
“…This is in contrast to a case series of 10 patients which found asymmetrical bullous changes on CT among chronic marijuana smokers but with normal spirometry and chest radiographs [37]. A study looking at smoking status and the presence of emphysematous computed tomography changes of spontaneous pneumothorax patients found no difference in emphysema prevalence among tobacco smokers and tobacco plus cannabis smokers (there were no cannabis only smokers); however, concurrent smokers were significantly younger [49]. While the authors have suggested that cannabis added to tobacco leads to emphysema at a younger age, there are too many confounders such as the subject population, to come to a definitive conclusion.…”
Section: Bullous Lung Diseasementioning
confidence: 60%
“…[9] and Ruppert and coll. [19] reported 102, 153 and 83 patients respectively who presented with spontaneous pneumothorax, of whom 17 (17%), 13 (8%) and 32 (38%) respectively smoked cannabis. In these studies CaS showed an higher incidence of lung bullae detected by CT-scan with respect to cannabis nonsmokers (tobacco smokers or nonsmokers).…”
Section: Plos Onementioning
confidence: 99%
“…Our patient with a history of heavy marijuana and tobacco smoking presented initially with a spontaneous pneumothorax that was drained via thoracosto-taneous pneumothorax. A retrospective cohort study by Ruppert, et al found that patients with a history of tobacco smoking were more likely to presentation with spontaneous pneumothorax at a much older age than those with a history of tobacco and cannabis smoking [7].…”
Section: Clinical Presentationmentioning
confidence: 99%